A reverse Warburg metabolism in oral squamous cell carcinoma is not dependent upon myofibroblasts. (25th November 2014) - Jensen, David H.; Therkildsen, Marianne H.; Dabelsteen, Erik
<x xml:space="preserve">Abstract</x> Background The reverse Warburg effect describes the phenomenon that epithelial cancer cells take advantage of the metabolic machinery from nearby cancer‐associated fibroblast, inducing them to produce lactate and ketones to fuel the high metabolic demands of the epithelial tumour tissues. This is in breast cancer observed as a lack of stromal caveolin‐1 (CAV‐1) and an increased expression of monocarboxylate transporter 4 (MCT‐4) in the tumour stroma, with a concomitant increase in the expression of monocarboxylate transporter 1 (MCT‐1) in the epithelial, tumour compartment. The lack of CAV‐1 and increased expression of MCT‐4 have been shown to have prognostic importance, primarily in patients with breast cancer. However, this phenomenon has only scarcely been described in oral squamous cell carcinoma (OSCC). Given the prognostic importance of myofibroblasts in OSCC, we also examined a potential relationship between the expression of MCT‐4 and the presence of myofibroblasts. Methods Paraffin‐embedded tissues from 30 patients with OSCC were immunostained with antibodies towards MCT‐1, MCT‐4, Cav‐1, GLUT‐1, α‐SMA, TOMM20 and KI‐67, and evaluated for their specific epithelial and stromal expression. Results and conclusions In patients with OSCC, we find an increased expression of MCT‐1 and MCT‐4 in both the epithelial and stromal compartment, with almost no overlap in their spatial expression. We found a large spatial overlap between α‐SMA and MCT‐1 in the stroma compartment, but no relationship between MCT‐4 and myofibroblasts. Interestingly, we did not observe any relationship between the absence of CAV‐1 and the presence of MCT‐4 as has been shown in breast carcinomas.